Uncovering Service Gaps in Hospitality: A Thematic Analysis of Guest Reviews for Service Quality Improvement - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi, 2025)
This study employs thematic analysis methodology to examine service quality dimensions through systematic investigation of 1,284 verified guest reviews at Katamaran Hotel & Resort Lombok, Indonesia. The research utilizes Atlas.ti software for rigorous coding and theme development, implementing a five-phase analytical framework encompassing data collection, preparation, coding analysis, theme development, and reporting. The findings reveal that guest satisfaction is predominantly influenced by three key factors: physical facility quality (9.4/10), staff performance (9.3/10), and service delivery mechanisms (9.2/10). Analysis identified specific service gaps requiring strategic intervention, particularly in response time optimization and interdepartmental coordination. The study establishes that successful service enhancement necessitates integration of standardized protocols across operational touchpoints, complemented by comprehensive staff development initiatives. Theoretical contributions include advancing understanding of service quality dynamics through sophisticated thematic analysis methodologies, establishing novel frameworks for service gap identification, and demonstrating effectiveness of integrated approaches to service quality enhancement. Practical implications provide hospitality managers with actionable insights for maintaining balanced focus across physical facility maintenance, staff training programs, and service delivery protocols. Future research directions suggest exploring artificial intelligence integration in service monitoring systems, developing predictive models for guest needs, and conducting cross-cultural analysis of service quality expectations in diverse hospitality contexts.